Online banking information systems acceptance: an empirical examination of system characteristics and web security - Chandio, Fida Hussain; Irani, Zahir; Zeki, Akram M.; Shah, Asadullah; Shah, Sayed Chhattan (Taylor & Francis Online, 2017)
Prior work on the technology acceptance model (TAM) is mainly devoted to the influence of TAM’s core motivational factors and their impact on behavioral intent toward IS acceptance. Relatively little research has focused on what specific system design characteristics motivate individuals toward IS acceptance. This article identified specific systems design factors and examined their impact on TAM’s motivational factors through the TAM. The findings will help designers to design and implement better user-accepted systems.